2013
DOI: 10.1073/pnas.1315155110
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of histone marks identifying an epigenetic signature of promoters and enhancers underlying cardiac hypertrophy

Abstract: Cardiac hypertrophy, initially an adaptive response of the myocardium to stress, can progress to heart failure. The epigenetic signature underlying this phenomenon is poorly understood. Here, we report on the genome-wide distribution of seven histone modifications in adult mouse cardiomyocytes subjected to a prohypertrophy stimulus in vivo. We found a set of promoters with an epigenetic pattern that distinguishes specific functional classes of genes regulated in hypertrophy and identified 9,207 candidate activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
175
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(186 citation statements)
references
References 36 publications
(41 reference statements)
9
175
0
Order By: Relevance
“…Genome-wide analysis of H3K27ac revealed that many loci are differentially associated with acetylated H3K27 during hypertrophy in mice (Papait et al, 2013). Close analysis of these data showed that H3K27ac levels were slightly increased at the promoter regions of Nppa and Nppb, but were not markedly changed in the −22 kb and −11 kb putative regulatory regions, in line with our findings.…”
Section: Discussion the Nppa-nppb Cluster Is Confined To A Regulatorysupporting
confidence: 90%
See 1 more Smart Citation
“…Genome-wide analysis of H3K27ac revealed that many loci are differentially associated with acetylated H3K27 during hypertrophy in mice (Papait et al, 2013). Close analysis of these data showed that H3K27ac levels were slightly increased at the promoter regions of Nppa and Nppb, but were not markedly changed in the −22 kb and −11 kb putative regulatory regions, in line with our findings.…”
Section: Discussion the Nppa-nppb Cluster Is Confined To A Regulatorysupporting
confidence: 90%
“…However, the −40/−35 kb region relative to Nppa, described above as a potential enhancer, was highly acetylated already in the normal heart (our data; Papait et al, 2013;Stamatoyannopoulos et al, 2012), and is likely to be involved in the adult expression of Nppb, which, in contrast to Nppa, is still expressed in the ventricles after birth. After TAC, the levels of H3K27ac in this region were significantly lower than in the normal heart.…”
Section: Discussion the Nppa-nppb Cluster Is Confined To A Regulatorymentioning
confidence: 52%
“…To gain insight into the role of DOT1L in cardiomyogenesis, we analyzed the genome-wide distribution of H3K79me2 in CMs during differentiation. To this end, we performed chromatin immunoprecipitation (ChIP) followed by massive parallel DNA sequencing (seq) for H3K79me2 and three other dynamic epigenetic marks of differentiation (i.e., H3K4me3, H3K27me3, and H3K9me3) on purified CMs isolated at two different stages of maturation: 1-day-old pup CMs (CMp), which are mononucleated cells that still retain proliferative capacity, and 2-month-old CMa, 15 which are mainly binucleated cells and have lost their ability to divide. 16 In addition, ChIP-seq data sets of mES from the Gene Expression Omnibus (GEO) database were used as reference points for cells in a pluripotent, undifferentiated state (GSE12241 and GSE11724).…”
Section: Resultsmentioning
confidence: 99%
“…Genome-wide localization of histone modifications (H3K4me3, H3K27me3, H3K79me2, and H3K9me3) for each stage was determined via ChIP followed by high-throughput seq with SoLiD 5500 (Life Technologies, Carlsbad, CA, USA) carried out as described elsewhere. 15 Briefly, 5 × 10 6 cells were used for each immunoprecipitation. Cells were cross-linked for 10 min at room temperature using 1% formaldehyde.…”
Section: Methodsmentioning
confidence: 99%
“…This program was initially developed for the identification of differential transcription factor binding to DNA (Ross-Innes et al, 2012) but recently, also used in a study on genomewide induced alterations in histone modifications in mice (Papait et al, 2013). DiffBind normalizes ChIPSeq samples for differences in peak calling and the amount of mapped reads enabling a direct quantitative comparison of histone modifications from different biological situations ("Materials and Methods").…”
Section: Assessment Of Data Qualitymentioning
confidence: 99%